Estate Taxation, Entrepreneurship, and Wealth - Cagetti, Marco; De Nardi, Mariacristina (American Economic Review, 2009)
This paper studies the estate tax in a quantitative framework with business investment, borrowing constraints, estate transmission, and wealth inequality. We find that the estate tax has little effect on the saving and investment decisions of small businesses, but does distort the decisions of larger firms, thereby reducing aggregate output and savings. Removing such distortions by eliminating the estate tax does not necessarily imply that everyone would be better off. If other taxes were raised to reestablish fiscal balance, those at the top of the wealth distribution would experience a large welfare gain, but most of the population would lose. (JEL D31, E21, H2)